Prospects for creating surfaces with vegetation on buildings in Poland - Ujma, Adam (Kyiv National University of Construction and Architecture, 2023)
According to the World Green Building Council, energy demand in buildings will increase double, by 2050. Worldwide, construction and the built environment contribute about 39% of global carbon dioxide (28% from operational emissions, from energy needed to heat, cool and power them, and the remaining 11% from materials and construction) and 50% of the world’s resource consumption. Thus, maximising energy efficiency and improving the environment are the main directions of construction development. Both tasks can be solved using green structures that connect living plants with building structures (green roofs, living facades and living interior walls). The data from the main organisations in the branch has been analysed: United Nations, The World Green Building Council, European Parlament and Council, and also Global Alliance for Buildings and Construction. They state the need for green and blue infrastructure, and sustainable urbanisation, incl. decarbonising of buildings and mitigation of urban heat islands. Greening of buildings is a measure to achieve the requirements. In addition, it improves health and well-being or increases biodiversity. Poland has the corresponding norms to stimulate the greening of buildings. The term “biologically active area” is defined as the area with an area arranged in a way that ensures natural vegetation of plants and rainwater retention; such an area also covers 50% of the surface of terraces and flat roofs with a vegetation layer with vegetation and other surfaces (e.g. green facade), providing natural vegetation of plants, with an area of not less than 10 m2, surface water in this area. Special tax policies give privileges to those who green their building(s). These measures have a good result in spreading green structures, which is proved by the objects represented in the article.